INTERPRETATION OF EUPHEMISMS USED IN SOCIAL LIFE (Scientific journal of the Fergana State University, 2024)
Speakers of different languages commonly use euphemisms to lessen the impact of ideas that might offend people or create social criticism. The media has been using euphemisms more frequently these days, and new, contentious euphemisms have also emerged. This article is also aimed at determining how necessary euphemisms are in people's lives and everyday life, in which the analysis of euphemisms that people use on a daily basis is carried out. We know that people are in constant communication in society. They show their signs and relations through language. In addition, they react to events positively or negatively in the society. People unknowingly use emoticons during communication. During this research, we found such expressions and analyzed them from the semantic, sociological, cultural and pragmatic points of view.